TA`TSIRU ISTIKHDAAMU WASAAITHA AL-GHAAZI AL-KALIMAAT AL-MUTAQAATHI’AH ILAA MAHAARAH KITAABAH AL-LUGHAH AL-‘ARABIYYAH LISHAF AT-TSAMIN FII AL-MADRASAH AT-TSANAWIYYAH “DARUL IHSAN” CIBUNGBULANG - Ulul Azmi; Asriani; Lukman Taufik Akasahtia (SHAWTUL ARAB, 2022)
Students often assume that learning Arabic is difficult. Game are an activity that has rules, purpose and fun. The playing of crossword puzzle is one of the Arabic learning media where students must fill the blank (white box) spaces with letters that from a word based on the instructions given. In addition, the game can be developed to train students to make perfect sentences from the root words that result from a crossword puzzle answer paragraph. This  research is meant to know impact on use of the medium crossword puzzle on the Arabic writing skills of class eight Junior High School Darul Ihsan Cibungbulang. The approach used in the study is the quantitative with experimental methods, While the research design uses a Pre-Experimental type One-Group Pretest Posttest Degsain. Data sources obtained from primary and secondary data. Data collection techniques use observation, interview, angket and test. Angket results and test are then treated using SPSS (Stastical Program For Sosial Sciences) for windows versi 26 dan Microsoft Excel 2010. Hypotheses in the test using Paired Sample t-Test. Based on data analysis, this studysuggests that the use of a medium of  crossword puzzle can affect the ability of the Arabic writing skills of class eight Junior High School Darul Ihsan Cibungbulang, with a Sig.(2-tailed) sum of 0,000<0,05